Corporate Social Responsibility Impact on Organization Performance's Sustainability in Educational Philantropic - Tarigan, Nuah P.; Purba, John Tampil; Harianja, Evo; Budiono, Sidik (Budapest International Research and Critics University, 2022)
Education is important for anyone, for anyone on this earth, in fact it is one of the main goals in the sustainable development goal, including those with disabilities, children and even those who are elderly. So we need a system that is sufficient to provide them with continuous, should not stop even if the economic, social and political conditions experience serious or critical problems. Social responsibility such as CSR plays a very important role, but we need to look at their existence one by one, because it does not all companies do not have a vision and even a mission in the fields related to Education, as we also know that the field of Education is not a mere profit-seeking institution income that must be earned in their financial context. A well-managed organization is certainly very much determined by the leadership and human resources they have in addition to other things that we will explore in the research that we will build. With a quantitative methodological approach going forward, because it will be more measurable and will be more in line with the situation. Further research will be continued so that the results found will be more valid.